Ölgemälde von Georgina Beier mit dem Titel Homage to Baba Lebe von 2004 (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Art; Painting; Artists; Women artists; Oil Painting